The Effects of Minimum Wage Increases on Poverty and Food Hardship - Lukas Lehner; Hannah Massenbauer; Zachary Parolin; Rafael Pintro Schmitt (Institute of Labor Economics (IZA), 2025)
We study how minimum wage (MW) increases affect poverty and food hardship in the United States from 1981 to 2019. Applying stacked difference-in-difference models and the Supplemental Poverty Measure (SPM), we find that a 1 MW increase reduces poverty by 0.3 to 0.7 percentage points among all working-age adults, and by 1.2 to 1.7 percentage points among individuals most likely to work in MW jobs. We also find that a 1 MW increase reduces food insufficiency by 1.5 percentage points among likely-MW workers. Effects on poverty are partially offset by higher living costs in MW-increasing states. Our findings are robust across methodological choices that have divided the recent literature. Overall, MW increases meaningfully reduce poverty and food hardship for the workers most directly affected and deliver modest improvements for the broader working-age population.
Keywords: I32; I38; J23; J38; J88; 330; minimum wages; poverty; food hardship; stacked difference-in-differences